1988
DOI: 10.1177/109019818801500203
|View full text |Cite
|
Sign up to set email alerts
|

Social Learning Theory and the Health Belief Model

Abstract: The Health Belief Model, social learning theory (recently relabelled social cognitive theory), self-efficacy, and locus of control have all been applied with varying success to problems of explaining, predicting, and influencing behavior. Yet, there is conceptual confusion among researchers and practitioners about the interrelationships of these theories and variables. This article attempts to show how these explanatory factors may be related, and in so doing, posits a revised explanatory model which incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

76
3,184
9
90

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 4,071 publications
(3,359 citation statements)
references
References 13 publications
76
3,184
9
90
Order By: Relevance
“…The findings can be interpreted within the Health Belief Model, a framework for relating factors that lead to change in health‐related behavior 25. Framing the severity of influenza as a health threat to individuals and household members who may be at higher risk, or relating the illness to lost wages due to missing work, may help communities understand the negative consequences in influenza infection.…”
Section: Discussionmentioning
confidence: 99%
“…The findings can be interpreted within the Health Belief Model, a framework for relating factors that lead to change in health‐related behavior 25. Framing the severity of influenza as a health threat to individuals and household members who may be at higher risk, or relating the illness to lost wages due to missing work, may help communities understand the negative consequences in influenza infection.…”
Section: Discussionmentioning
confidence: 99%
“…25 Therefore 25 researchers need to understand the facilitators and barriers to engaging in exercise in the post 26 discharge period. Previous studies have concluded that older peoples' attitudes and beliefs 27 affect their adherence to falls prevention and other exercise programs 15-17, 20, 26 and therefore 28 should be measured together with other factors of interest. The Health Belief Model (HBM) 29 is a recognised health behavior model 27 that provides an empirically supported framework to 30 measure these factors and has been used previously to understand older peoples' awareness 31 and self perceived risk of falls and falls injuries.…”
mentioning
confidence: 99%
“…Previous studies have concluded that older peoples' attitudes and beliefs 27 affect their adherence to falls prevention and other exercise programs 15-17, 20, 26 and therefore 28 should be measured together with other factors of interest. The Health Belief Model (HBM) 29 is a recognised health behavior model 27 that provides an empirically supported framework to 30 measure these factors and has been used previously to understand older peoples' awareness 31 and self perceived risk of falls and falls injuries. 28,29 The HBM conceptualises that a person 32 will engage in protective health behavior if they: i) perceive they are at risk of contracting a 33 negative health condition; ii) perceive that its consequences will be severe enough to 34 adversely affect their health; iii) consider that the benefits of engaging in the health behavior 35 outweigh the costs of undertaking it; iv) receive a cue to engage in the behavior.…”
mentioning
confidence: 99%
See 2 more Smart Citations